PENGARUH FINANCIAL DISTRESS DAN CORPORATE GOVERNANCE TERHADAP KECEPATAN PUBLIKASI LAPORAN KEUANGAN TAHUNAN - Simamora, Klarita Pitrusani Octavia; Aristi, Mentari Dwi; Samsiah, Siti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The matter of submitting annual financial reports on time greatly affects the quality of the financial report itself. Financial reports are said to be of quality when information is presented on time and available when needed. The purpose of this study is to determine whether the condition of financial distress and the form of corporate governance of a company affect the speed of publication of annual financial reports. The study was conducted on companies engaged in the property and real estate sector and listed on the Indonesia Stock Exchange in 2021-2022. The purposive sampling technique was used to select samples with a total of 140 samples. The data in the study are secondary data. The data analysis technique is multiple linear analysis. The results of the study show that financial distress and corporate governance represented by managerial ownership and audit quality do not affect the speed of publication of annual financial reports. Meanwhile, corporate governance represented by independent commissioners, institutional ownership and audit committees have a negative effect on the speed of publication of annual financial reports